2017
DOI: 10.4317/jced.53262
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of intraalveolar placement of combination of 0.2% chlorhexidine and 10 Mg metronidazole gel on the occurrence of dry sockets- A randomized control trial

Abstract: BackgroundTo evaluate the effects of intraalveolar placement of gel containing 0.2% chlorhexidine and 10gm of metronidazole on the incidence of alveolar osteitis.Material and MethodsA total of 300 impacted third molars were extracted in 150 patients enrolled in this trial. In each subject a socket was randomly selected and packed to the crest of alveolar ridge with the gel. The contralateral socket was packed with placebo dressing. The occurrence of dry socket was assessed during 3rd and 5th postoperative days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…Therefore, since no other studies in the field of oral surgery have used a SOS, the present study carried out the first comparison of this compound with the gold standard used in these situations, chlorhexidine. Multiple studies can support this affirmation that chlorhexidine is the gold standard ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, since no other studies in the field of oral surgery have used a SOS, the present study carried out the first comparison of this compound with the gold standard used in these situations, chlorhexidine. Multiple studies can support this affirmation that chlorhexidine is the gold standard ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 92%
“…In the study group, the combination of metronidazole with chlorhexidine gel was introduced. In the study group, the incidence of alveolitis was significantly reduced, from 22.6% to 6.6% ( p ≤ 0.001); therefore, they concluded that the intraalveolar use of this gel decreases the incidence of adverse reactions and complications related to the extraction of lower third molars ( 28 ).…”
Section: Discussionmentioning
confidence: 92%
“…Epidemiological studies have revealed several contradictory risk factors in the development of post-extraction alveolitis: surgical trauma as a consequence of the difficulty in extraction and/or inexperience of the surgeon, inadequate intraoperative irrigation, use of oral contraceptives and/or immunosuppression, advanced age, female sex and smoking. However, the true causes of the condition are not known [ 2 , 7 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CHX gluconate gel 0.2% is characterized by higher bioadhesive properties and is more effective than CHX gluconate solution 0.12% Hita-Iglesias et al [97] . What is more, the results of the meta-analysis showed that using topical metronidazole and CHX gel is effective in reducing AO [98] .…”
Section: Chlorhexidinementioning
confidence: 96%